STABILITY OF CLOSEDNESS OF CONVEX CONES UNDER LINEAR MAPPINGS II - Borwein, J. M.; Moors, W. B. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper we revisit the question of when the continuous linear image of a fixed closed convex cone K is closed. Specifically, we improve the main result of [3] by showing that for all, except for at most a s-porous set, of the linear mappings T from Rn into Rm, not only is T(K) closed, but there is also a neighbourhood around T whose members also preserve the closedness of K.